Identification and Characterization of oriT and Two Mobilization Genes Required for Conjugative Transfer of Salmonella Genomic Island 1 - Kiss, János; Szabó, Mónika; Hegyi, Anna; Douard, Gregory; Praud, Karine; Nagy, István; Olasz, Ferenc; Cloeckaert, Axel; Doublet, Benoît (Frontiers in Microbiology, 2019)
The integrative mobilizable elements of SGI1-family considerably contribute to the spread of resistance to critically important antibiotics among enteric bacteria. Even though many aspects of SGI1 mobilization by IncA and IncC plasmids have been explored, the basic transfer elements such as oriT and self-encoded mobilization proteins remain undiscovered. Here we describe the mobilization region of SGI1 that is well conserved throughout the family and carries the oriTSGI1 and two genes, mpsA and mpsB (originally annotated as S020 and S019, respectively) that are essential for the conjugative transfer of SGI1. OriTSGI1, which is located in the vicinity of the two mobilization genes proved to be a 125-bp GC-rich sequence with several important inverted repeat motifs. The mobilization proteins MpsA and MpsB are expressed from a bicistronic mRNA, although MpsB can be produced from its own mRNA as well. The protein structure predictions imply that MpsA belongs to the lambda tyrosine recombinase family, while MpsB resembles the N-terminal core DNA binding domains of these enzymes. The results suggest that MpsA may act as an atypical relaxase, which needs MpsB for SGI1 transfer. Although the helper plasmid-encoded relaxase proved not to be essential for SGI1 transfer, it appeared to be important to achieve the high transfer rate of the island observed with the IncA/IncC-SGI1 system.